Introduction to population genetics 2: linkage disequilibrium - Balding, David; Morris, Andrew (Henry Stewart Talks, 2004)
Overview of part 1, Two-locus Wright-Fisher model, Ancestral Recombination Graph (ARG), Measures of LD, Disease-marker association, LD due to linkage, LD due to admixture, Haplotype sharing, LD in human populations: empirical studies, Haplotype blocks
Archived at 2021/02/25